Pemanfaatan Teknik Content Based Image Retrieval Berbasis Sketsa Untuk Pengenalan Wajah Dengan Pose Normal - Hasibuan, Muhammad Said; Nugroho, Handoyo Widi (Proceedings Konferensi Nasional Sistem dan Informatika (KNS&I), 2015)
As the rising up crimes including teror in our society due to politics issues, economy, poverty, religion and ethnic conflicts. Many ways and techniques have been tried to crack down those crimes but unfortunately the efforts to seize person or group of criminal suspected is far from our expectation. Face recognition is one of techniques introduced by many researchers for the last decades with many methods and approaches they tried to recognize a person based on his or his faces. Some of the methods such as face recognition with Query by Example (QBE) using shape, colour, and texture to match a query face with face in the database; however the result is not good enough to recognize the faces. One of the problems of face recognition by QBE is sometime we do not have a picture or face image to make QBE. In order to sort it out the problem, in this research we will try to introduce of face recognition method by generating a face image by a face sketch. Many sketch based face recognition was introduced by some researchers and experts, but most of their methods have been applied directly inputting a sketch into database which is very costly and involved a complex algorithm. In addition to the research, we are applying our method proposed into compressed face images, as the compressed images will save storage and simplifier the algorithm.